EFFECT OF IMPREGNATION PROCEDURE OF Pt/γ-AL2O3 CATALYSTS UPON CATALYTIC OXIDATION OF CO - Triyono Triyono (Indonesian Journal of Chemistry, 2003)
The oxidation of carbon monoxide by oxygen using two catalysts prepared by two different methods has been investigated. In the first method, catalyst prepared by immersing γ-Al2O3 into the hexa-chloroplatinic acid solution at 80oC for 4 h, resulted Pt/γ-Al2O3 catalyst having platinum highly dispersed on the support. While that of immersing γ-Al2O3 in the hexa-chloroplatinic acid solution at room temperature for 12 h, produced Pt/ γ-Al2O3 catalyst where platinum dispersion was much lower. Catalytic activity test showed that platinum well dispersed on the support enhanced the activity for oxidation of carbon monoxide. The platinum impregnated at room temperature resulted in the poor activity.